High-safety and long-service-life high-energy lithium battery local high-concentration electrolyte and application thereof
By using low -response thermal lithium salt and high polarity solvents in lithium battery electrolytes, the solvent sheath structure is constructed, and the existing flame retardant LHCE reactions under abnormal conditions have been solved, and the high safety performance of the battery is realized. And long cycle life.
Patent Information
- Application Number
- CN202411361385.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing flame retardant LHCE will still undergo a violent exothermic reaction with the battery electrode material under abnormal operating conditions, causing the battery to get out of control.
Lithium salt with low -reactive thermal, such as lithium ostefluorofluororam, combined with thinner solvents and small exnsureables to build a solvent sheath structure, promote the formation of effective SEI, and improve the electrolyte anode stability.
A significant reduction of the reaction heat of the electrolyte, improving the safety performance of the battery level, and achieving the organic combination of long -cycle life and high safety performance of high -energy lithium batteries.
Smart Images

Figure CN119381548A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery electrolytes, and more specifically, relates to a high-energy lithium battery local high-concentration electrolyte with high safety and long life and its application. Background Art
[0002] The electrolyte used in traditional commercial lithium-ion batteries usually dissolves lithium hexafluorophosphate in ethylene carbonate and linear carbonates such as ethyl methyl carbonate and dimethyl carbonate. Due to the use of a large amount of organic solvents, conventional electrolyte systems are highly flammable. In addition, conventional electrolytes will undergo violent exothermic reactions with battery electrode materials under abnormal operating conditions (such as puncture, overheating, overcharging, etc.), causing battery thermal runaway. The flammability and high reactivity of conventional electrolytes are important factors affecting the overall safety performance of batteries. Initially, in order to improve the safety performance of lithium-ion batteries, researchers introduced phosphorus-containing flame retardants to suppress the flammability of batteries. However, while controlling the flammability of the battery, the introduction of phosphorus-containing flame retardants also hindered the formation of the solid electrolyte interface (SEI) on the graphite negative electrode interface, resulting in a significant decrease in battery performance; in addition, considering the comprehensive safety performance at the battery level, while achieving the flame retardant effect, the reactivity between the electrolyte and the electrode material should also be considered. In order to better achieve safety performance at high energy density, it is necessary to develop a new and effective lithium-ion battery electrolyte system.
[0003] The emergence of local high concentration electrolyte (LHCE) solves the problem of incompatibility between flame retardants and graphite negative electrodes, making it possible to use flame retardants as the main solvent of the electrolyte. At present, researchers have designed a variety of flame retardant-based LHCEs, which can not only achieve flame retardancy, but also achieve a cycle life significantly better than conventional electrolytes in lithium-ion batteries. However, the existing flame-retardant LHCEs mainly use lithium bis(fluorosulfonyl)imide and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether as lithium salts and diluents, and lithium bis(fluorosulfonyl)imide has been proven to have severe exothermic reactions with electrodes, leading to thermal runaway of the battery. The exothermic reaction between the electrolyte and the electrode material at high temperature is a more dangerous factor than the flammability of the electrolyte itself. For example, the inventor team prepared a dual flame retardant (DFR) electrolyte in the previous study (Jia H, Yang Z, Xu Y, et al. Is nonflammability of electrolyte overrated in the overall safety performance of lithium ion batteries? A sobering revelation from a completely nonflammable electrolyte [J]. Advanced Energy Materials, 2023, 13 (4): 2203144.), using lithium bis(fluorosulfonyl)imide as lithium salt, trimethyl phosphate (TMPa) as solvent, tris(2,2,2-trifluoroethyl)phosphite (TTFEPi) as diluent, and ethylene carbonate (EC) as additive, which not only achieved the complete non-flammability of LHCE (its liquid phase and vapor are both flame retardant), but also achieved a solvated structure. Although the DFR electrolyte exhibits strict non-flammability, both the penetration test and the overheating test show that at the battery level, the DFR electrolyte is not as safe as the traditional lithium battery electrolyte and cannot achieve battery-level safety performance. That is, unilaterally reducing the flammability of the electrolyte is far from enough to improve the safety performance of the battery level, and reducing the reactivity between the electrolyte and the charging electrode should also be considered.
[0004] Therefore, it is necessary to explore and establish a richer lithium salt-solvent-diluent system to further expand the spectrum of LHCE and better realize the organic combination of high energy density, long cycle life and high safety performance of lithium-ion batteries. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the existing flame-retardant LHCE, which, although completely non-flammable, still undergoes a violent exothermic reaction with the battery electrode material under abnormal operating conditions (such as puncture, overheating, overcharging, etc.), causing thermal runaway of the battery, and provide a local high-concentration electrolyte for a lithium battery. The local high-concentration electrolyte for a lithium battery reduces the reaction heat of the LHCE while retaining the structural advantages of the LHCE, thereby improving the safety performance at the battery level.
[0006] Another object of the present invention is to provide an application of the lithium battery local high concentration electrolyte in the preparation of lithium ion batteries.
[0007] Another object of the present invention is to provide a lithium ion battery.
[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0009] The present invention protects a local high-concentration electrolyte for a lithium battery, wherein the local high-concentration electrolyte for a lithium battery comprises a lithium salt, a solvent, and a diluent;
[0010] Wherein, the solvent comprises at least one of the following reagents: sulfolane, dimethyl sulfone, dimethyl sulfoxide, ethyl methyl sulfone, 3-methyl sulfolane, ethylene sulfite, ethyl isopropyl sulfone, trimethyl phosphate, tributyl phosphate, dimethyl methyl phosphate, ethylene ethyl phosphate, trifluoroethyl methanesulfonate;
[0011] The diluent comprises at least one of the following reagents: tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) ethyl phosphate, bis(2,2,2-trifluoroethyl) methyl phosphate, triphenyl phosphate, hexafluorocyclotriphosphazene, (trifluoroethoxy) pentafluorocyclotriphosphazene, (phenoxy) pentafluorocyclotriphosphazene, pentafluorophenyl diphenyl phosphate, tris(pentafluorophenyl) phosphine;
[0012] The lithium salt does not include lithium bis(fluorosulfonyl)imide;
[0013] The mass proportion of the diluent in the local high-concentration electrolyte of the lithium battery is 30% to 80%; the mass proportion of the additive in the local high-concentration electrolyte of the lithium battery is 0% to 20%.
[0014] Although the existing flame-retardant LHCE has achieved complete non-flammability, it will still react violently with the battery electrode material under abnormal conditions (such as puncture, overheating, overcharging, etc.), causing the problem of thermal runaway of the battery. The present invention has developed a flame-retardant, low-reaction heat LHCE, using low-reaction heat lithium salt to replace lithium bis(fluorosulfonyl)imide (LiFSI), and exploring safe and stable solvents and diluents compatible with it. These components work together to obtain an electrolyte with good electrochemical performance and high safety. Among them, the high-polarity solvent and the lithium salt with low heat release constitute a solvent sheath structure, which promotes the formation of an effective SEI, improves the stability of the electrolyte anode, and achieves a long cycle life of a high-energy lithium battery. The diluent can reduce the viscosity of the electrolyte, which is beneficial for the electrolyte to infiltrate the diaphragm, while improving the flame retardant properties of the electrolyte, and does not interfere with the long cycle performance of the battery. The additive is only used to improve the formation of an effective SEI and further improve the long cycle performance of the battery. Whether it is added or not does not affect the solvent sheath structure and flame retardant properties of the resulting electrolyte.
[0015] Preferably, the additive includes at least one of the following reagents: fluoroethylene carbonate, difluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, vinyl ethylene carbonate, propylene carbonate, vinyl sulfate, and vinyl sulfite.
[0016] Preferably, the additive accounts for 0% to 20% by mass of the local high-concentration electrolyte of the lithium battery.
[0017] More preferably, the additive accounts for 1% to 10% by mass of the local high-concentration electrolyte of the lithium battery.
[0018] Preferably, the lithium salt includes at least one of the following reagents: lithium tetrafluoroborate, lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(trifluoromethane)sulfonyl imide, lithium fluorododecaborane, lithium tetrakis(trifluoromethyl)borate, lithium tetrakis(pentafluorophenyl)borate, lithium tetracyanoborate, lithium dioxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium methanedisulfonate difluoroborate, lithium (2-fluoromalonate) difluoroborate, lithium bismalonate borate, lithium difluorophosphoryl trifluoroborate, lithium di(difluorophosphoryloxy) difluoroborate, lithium tetrakis(difluorophosphoryloxy)borate, lithium tetrafluorooxalate phosphate, lithium tetrafluorobisoxalate phosphate.
[0019] Preferably, the mass proportion of the diluent in the local high-concentration electrolyte of the lithium battery is 40% to 70%.
[0020] Preferably, the mass proportion of the solvent in the local high-concentration electrolyte of the lithium battery is 20% to 70%.
[0021] More preferably, the mass proportion of the solvent in the local high-concentration electrolyte of the lithium battery is 20% to 50%.
[0022] Preferably, the lithium salt accounts for 5% to 20% by mass of the local high-concentration electrolyte of the lithium battery.
[0023] More preferably, the lithium salt accounts for 8% to 20% by mass of the local high-concentration electrolyte of the lithium battery.
[0024] Preferably, the concentration of lithium ions in the lithium salt in the local high-concentration electrolyte of the lithium battery is 1 to 3 mol / L (M).
[0025] Furthermore, the molar ratio of the lithium salt, the solvent, the diluent and the additive is 1:(1-3):(1-3):(0-1).
[0026] Preferably, the molar ratio of the lithium salt, the solvent, the diluent and the additive is 1:(1-2.5):(1-2.5):(0-0.5).
[0027] The present invention also protects the use of the local high-concentration electrolyte of the lithium battery in the preparation of lithium-ion batteries.
[0028] The present invention also protects a lithium ion battery, comprising a positive electrode, a negative electrode and a local high-concentration electrolyte of the lithium battery.
[0029] Compared with the prior art, the present invention has the following beneficial effects: the local high-concentration electrolyte of the lithium battery of the present invention includes a lithium salt, a solvent, and a diluent, providing a highly safe lithium salt-solvent-diluent combination system at the battery level, and adding additives on this basis can further improve the specific capacity and long-term cycle performance of the lithium battery. The above electrolyte not only significantly improves the overall safety performance of the lithium battery, but also enables the high-energy-density lithium-ion battery to maintain high capacity and long life at a high-voltage (greater than 4.2V) charging cut-off voltage, and has broad application value in flame-retardant lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The battery specific capacity performance curves are obtained by using the electrolyte prepared in Example 1 of the present invention (E-SE-F for short), the electrolyte prepared in Example 3 (E-SE for short), and the conventional commercial electrolyte prepared in Comparative Example 1 (E-Baseline for short) as graphite||NMC lithium-ion battery electrolytes in a long cycle test of 500 cycles of charge and discharge at a charge rate of 0.33C and a discharge rate of 1C.
[0031] Figure 2The schematic diagram of the microscopic solvent sheath structure of Example 3 (Figure (a)) and Example 1 (Figure (b)) under molecular dynamics simulation of the present invention. Different atoms are distinguished by different colors: gray represents C; red represents O; green represents Li; pink represents B; cyan represents F; purple represents P; yellow represents S; white represents H. For clearer observation, the diluent is simplified in the form of lines.
[0032] Figure 3 Comparative graphs of the flammability tests of the conventional commercial electrolyte prepared in comparative example 1 of the present invention (Figure (a)), the electrolyte prepared in Example 3 (Figure (b)), and the electrolyte prepared in Example 1 (Figure (c)); and comparative graphs of the combustion phenomena of the conventional commercial electrolyte (Figure (d)), the electrolyte prepared in Example 3 (Figure (e)), and the electrolyte prepared in Example 1 (Figure (f)) after the fire source is removed.
[0033] Figure 4 The puncture test phenomena of the electrolyte prepared in Example 1 of the present invention (abbreviated as E-SE-F) in the application of battery-grade graphite||NMC soft-pack batteries and the temperature and voltage change curves in the puncture test.
[0034] Figure 5 The puncture test phenomena of the conventional commercial electrolyte (E-Baseline for short) prepared in Comparative Example 1 in the application of battery-grade graphite||NMC soft-pack batteries and the temperature and voltage change curves in the puncture test. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0036] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0037] The preparation of the electrolyte was carried out in a glove box filled with argon at room temperature. The oxygen and water content in the glove box was kept below 0.01 ppm.
[0038] Example 1 Preparation of Local High-Concentration Electrolyte for Lithium Batteries
[0039] Preparation of battery electrolyte: Lithium tetrafluoroborate was dissolved in cyclopentane sulfone at a molar ratio of lithium salt to solvent of 1:2, and after stirring overnight, an equal molar amount of diluent tris(2,2,2-trifluoroethyl) phosphate was added as lithium tetrafluoroborate, followed by an additive fluoroethylene carbonate in an amount of one-fifth of the molar amount of lithium tetrafluoroborate to form a safe electrolyte.
[0040] Among them, in terms of mass percentage of the electrolyte, the mass percentage of lithium tetrafluoroborate is 13.4% (the concentration of lithium salt in the electrolyte is 2 mol / L), the mass percentage of cyclopentane sulfone is 34.4%, the mass percentage of tri(2,2,2-trifluoroethyl) phosphate is 49.2%, and the mass percentage of fluoroethylene carbonate is 3.0%.
[0041] Example 2 Preparation of Local High-Concentration Electrolyte for Lithium Batteries
[0042] The difference from Example 1 is that the mass proportions of lithium salt, solvent, diluent and additive are different. The specific preparation comprises the following steps:
[0043] Preparation of battery electrolyte: Lithium tetrafluoroborate was dissolved in sulfolane at a molar ratio of lithium salt to solvent of 1:2, and after stirring overnight, tri(2,2,2-trifluoroethyl) phosphate, a diluent, in an amount equal to that of sulfolane was added, followed by the addition of fluoroethylene carbonate, an additive, in an amount equal to one-fifth of the molar amount of lithium tetrafluoroborate, to form a safe electrolyte.
[0044] Among them, calculated by mass percentage of the electrolyte, the mass percentage of lithium tetrafluoroborate is 9.0% (the concentration of lithium salt in the electrolyte is 2 mol / L), the mass percentage of cyclopentane sulfone is 23.0%, the mass percentage of tri(2,2,2-trifluoroethyl) phosphate is 66.0%, and the mass percentage of fluoroethylene carbonate is 2.0%.
[0045] Example 3 Preparation of lithium battery electrolyte
[0046] The difference from Example 1 is that there is no additive. The specific preparation comprises the following steps:
[0047] Preparation of battery electrolyte: dissolve lithium tetrafluoroborate in sulfolane at a molar ratio of lithium salt to solvent of 1:2, stir overnight, and add diluent tris(2,2,2-trifluoroethyl) phosphate in an equal molar amount to lithium tetrafluoroborate to form a safe electrolyte. Among them, the mass percentage of lithium tetrafluoroborate is 13.8% (the concentration of lithium salt in the electrolyte is 2 mol / L), the mass percentage of sulfolane is 35.5%, and the mass percentage of tris(2,2,2-trifluoroethyl) phosphate is 50.7%.
[0048] Comparative Example 1 Preparation of conventional lithium battery electrolyte
[0049] Preparation of battery electrolyte: Ethylene carbonate and ethyl methyl carbonate were uniformly mixed in a mass ratio of 3:7, and the mixed solvent was added into a quantitative lithium hexafluorophosphate to fully dissolve to form a conventional commercial electrolyte with a lithium salt concentration of 1 mol / L as a control group.
[0050] The above conventional commercial electrolyte takes 25mL as an example, and the specific preparation is as follows:
[0051] S1. Preparation of EC / EMC solution: Ethylene carbonate and ethyl methyl carbonate were uniformly mixed in a mass ratio of 3:7 to obtain EC / EMC solution;
[0052] S2. Weigh 3.7978 g of LiPF6, add a small amount of EC / EMC solution obtained in step S1 to dissolve, transfer to a 25 mL volumetric flask, and then add EC / EMC solution to make the volume up to 25 mL, thus forming a conventional commercial electrolyte with a lithium salt concentration of 1 mol / L.
[0053] The electrolyte components and the proportions of the components in the electrolyte in the embodiments and comparative examples provided by the present invention are shown in Table 1.
[0054] Table 1 Electrolyte components and mass percentage of each component in the electrolyte in the embodiments provided by the present invention
[0055]
[0056] Experimental Example 1 Preparation of lithium battery and its performance test
[0057] (1) Battery cycle performance test
[0058] The electrolytes obtained in Example 1 and Example 3 were used as representative local high-concentration electrolytes and further prepared into lithium batteries for cycle performance testing.
[0059] Preparation of lithium battery: The cut graphite pole piece with a diameter of 14 mm and the NMC811 pole piece with a diameter of 12 mm were vacuum dried at 110°C for 12 hours and then transferred to a glove box filled with argon. Each button cell is assembled from an NMC811 pole piece, a polypropylene diaphragm with a diameter of 19 mm, a graphite pole piece, a gasket, a spring and 50 μL of electrolyte (electrolyte prepared in Example 1, Example 3 and Comparative Example 1). To prevent stainless steel from suffering from anode corrosion under high pressure, all button cells use an aluminum-plated positive electrode shell and an additional aluminum foil with a diameter of 19 mm placed on the aluminum-plated positive electrode shell.
[0060] The button cell prepared above was placed in a thermostat (LONGYUE LBI-250) connected to a LAND battery test system (CT2001A) and left to stand for 12 hours. After the standing period, the battery was charged and discharged once at a rate of 0.05C, and then twice at a rate of 0.1C to promote the formation of SEI. After SEI formation, the long-term cycle performance of the graphite||NMC811 battery was evaluated by charging at a rate of 0.33C and discharging at a rate of 1C for 500 cycles, and the battery charge and discharge cut-off voltage was controlled at 2.5V-4.4V. The battery cycle life is as follows Figure 1 As shown, in the long-term cycle test of the battery, after 500 cycles, since no additives were added to Example 3, the specific capacity and capacity retention rate of the battery (115.5 mAh / g, 66.2%) were the same as the lithium battery of Comparative Example 1 (116.0 mAh / g, 67.5%); after adding a small amount of additives to Example 1, it can be significantly observed that the specific capacity and capacity retention rate of the battery (127.5 mAh / g, 70.1%) are significantly improved compared with Comparative Example 1 and Example 3.
[0061] The specific capacity and capacity retention rate of the lithium battery prepared using the electrolyte obtained in Example 2 are better than those in Comparative Example 1, and the cycle performance test is similar to that of the lithium battery obtained in Example 1, which will not be repeated here.
[0062] (2) Molecular dynamics calculations
[0063] The lithium salt, solvent, diluent and additive molecules of Example 1 or Example 3 (the component has no additive) were randomly inserted into the molecular dynamics simulation box according to the experimental proportion and density to construct the original structural model of the lithium salt / solvent / diluent / additive mixed system. All systems were pre-balanced for 5ps, simulated for 50ps, and the time step was 1fs in the simulation calculation. The result schematic diagram is shown in Figure 2 As shown, the lithium salt and solvent molecules in Example 3 of the present invention have a tendency to form a solvation structure in the electrolyte, thereby forming a solvent sheath structure ( Figure 2 (a)) of the local high concentration electrolyte, and after the introduction of a small amount of additives (Example 1), the solvent sheath structure of the local high concentration electrolyte can still remain intact ( Figure 2 (b)).
[0064] (3) Flammability test
[0065] The electrolytes obtained in Example 1 and Example 3 were used as representative local high-concentration electrolytes to conduct flammability tests.
[0066] The flammability of the electrolyte is determined by an ignition test. 200 μL of the electrolyte sample is dripped onto a non-flammable glass fiber filter paper (Whatman, GF / D), and the sample is ignited with a butane flame for 1 second. The ignition and combustion of the electrolyte are continuously recorded with a digital camera. The flammability test results are shown in Figure 1. Figure 3As shown, (a), (b), and (c) are the flammability tests of Comparative Example 1, Example 3, and Example 1, respectively, and (d), (e), and (f) are the phenomena of Comparative Example 1, Example 3, and Example 1 after the test was completed and the fire source was removed, respectively. It can be seen from the figure that the glass fiber paper to which the electrolyte obtained in Comparative Example 1 was added was immediately ignited and continued to burn in the air, while the glass fiber paper to which the electrolytes of Examples 1 and 3 were added could not be ignited by an external heat source, and had a significant flame retardant effect. It can be seen that the additive is only used to improve the formation of an effective solid electrolyte interface film (Solid Electrolyte Interphase, SEI), to enhance the initial specific capacity and cycle performance of the battery, and is not related to the electrolyte solvent sheath structure and flame retardant properties. The other properties of Example 3 are basically the same as those of Example 1.
[0067] (4) Soft-pack battery puncture test
[0068] The electrolyte obtained in Example 1 was used as a representative local high-concentration electrolyte to conduct a soft-pack battery puncture test.
[0069] The electrolyte obtained in Example 1 or Comparative Example 1 was injected into a commercial graphite||NMC721 soft-pack battery (1.8Ah), charged to 4.3V by CCCV and placed in a test box. A 3mm diameter steel nail was inserted into the geometric center of the battery for at least 1 minute, during which the battery temperature and voltage were monitored by an electrochemical workstation and a temperature sensor, respectively. Within 10 to 20 minutes after the penetration was completed, the real-time changes in temperature and voltage were continuously recorded. The soft-pack battery puncture test results are shown in Figure 2. Figure 4 , 5 As shown in the figure, the soft-pack battery of Example 1 passed the puncture test safely, while the soft-pack battery prepared in Comparative Example 1 caught fire immediately after being punctured. After puncture, the temperature of the soft-pack battery of Example 1 changed very little, rising from 32°C to 35°C and then remained stable. The voltage value was also very stable. Except for a slight fluctuation in the voltage at the beginning of the test, the voltage value was stable above 4.1V ( Figure 4 In contrast, the temperature of the soft-pack battery prepared in Comparative Example 1 quickly rose to a maximum of 514.3°C. After puncture, the battery short-circuited and the voltage dropped cliff-like, immediately dropping to 0V ( Figure 5 ).
[0070] The inventor team prepared a dual flame retardant (DFR) electrolyte in the previous study (Jia H, Yang Z, Xu Y, et al. Is nonflammability of electrolyte overrated in the overall safety performance of lithium ion batteries? Asobering revelation from a completely nonflammable electrolyte [J]. Advanced Energy Materials, 2023, 13 (4): 2203144.), using lithium bis(fluorosulfonyl)imide as lithium salt, trimethyl phosphate (TMPa) as solvent, tris(2,2,2-trifluoroethyl)phosphite (TTFEPi) as diluent, and ethylene carbonate (EC) as additive, which not only achieved the complete non-flammability of LHCE (both its liquid phase and vapor are flame retardant), but also realized the solvation structure. Although the DFR electrolyte exhibits strict non-flammability, both the penetration test and the overheat test show that, at the battery level, the DFR electrolyte is not as safe as the traditional lithium battery electrolyte (i.e., the electrolyte of Comparative Example 1), and cannot achieve battery-level safety performance. The electrolyte of the present application not only has excellent flame retardant properties, but also achieves battery-level safety performance, which is a significant improvement.
[0071] The soft-pack battery injected with the electrolyte obtained in Example 2 has basically the same puncture test results as the soft-pack battery obtained in Example 1, and has excellent battery-level safety performance, which will not be repeated here.
[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A lithium battery local high concentration electrolyte, characterized in that: The local high-concentration electrolyte of the lithium battery includes lithium salt, solvent, diluent and additive; Wherein, the solvent comprises at least one of the following reagents: sulfolane, dimethyl sulfone, dimethyl sulfoxide, ethyl methyl sulfone, 3-methyl sulfolane, ethylene sulfite, ethyl isopropyl sulfone, trimethyl phosphate, tributyl phosphate, dimethyl methyl phosphate, ethylene ethyl phosphate, trifluoroethyl methanesulfonate; The diluent comprises at least one of the following reagents: tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) ethyl phosphate, bis(2,2,2-trifluoroethyl) methyl phosphate, triphenyl phosphate, hexafluorocyclotriphosphazene, (trifluoroethoxy) pentafluorocyclotriphosphazene, (phenoxy) pentafluorocyclotriphosphazene, pentafluorophenyl diphenyl phosphate, tris(pentafluorophenyl) phosphine; The lithium salt does not include lithium bis(fluorosulfonyl)imide; The mass proportion of the diluent in the local high-concentration electrolyte of the lithium battery is 30% to 80%; the mass proportion of the additive in the local high-concentration electrolyte of the lithium battery is 0% to 20%.
2. The lithium battery local high concentration electrolyte according to claim 1, characterized in that: The additive comprises at least one of the following reagents: fluoroethylene carbonate, difluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, vinyl ethylene carbonate, propylene carbonate, vinyl sulfate, and vinyl sulfite.
3. The local high concentration electrolyte of a lithium battery according to claim 1, characterized in that: The lithium salt includes at least one of the following reagents: lithium tetrafluoroborate, lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(trifluoromethane)sulfonyl imide, lithium fluorododecaborane, lithium tetra(trifluoromethyl)borate, lithium tetra(pentafluorophenyl)borate, lithium tetracyanoborate, lithium bisoxalateborate, lithium difluorooxalateborate, lithium trifluoromethanesulfonate, lithium methanedisulfonate difluoroborate, lithium (2-fluoromalonate) difluoroborate, lithium bismalonateborate, lithium difluorophosphoryloxy trifluoroborate, lithium bis(difluorophosphoryloxy) difluoroborate, lithium tetra(difluorophosphoryloxy)borate, lithium tetrafluorooxalatephosphate, lithium tetrafluorobisoxalatephosphate.
4. The local high concentration electrolyte of a lithium battery according to claim 1, characterized in that: The lithium salt accounts for 5% to 20% by mass of the local high-concentration electrolyte of the lithium battery.
5. The local high concentration electrolyte of a lithium battery according to claim 1, characterized in that: The concentration of lithium ions in the lithium salt in the local high-concentration electrolyte of the lithium battery is 1 to 3 mol / L.
6. The local high concentration electrolyte of a lithium battery according to claim 1, characterized in that: The mass proportion of the diluent in the local high-concentration electrolyte of the lithium battery is 40% to 70%.
7. The lithium battery local high concentration electrolyte according to claim 1, characterized in that: The mass proportion of the solvent in the local high-concentration electrolyte of the lithium battery is 20% to 70%.
8. The local high concentration electrolyte of a lithium battery according to claim 1, characterized in that: The molar ratio of the lithium salt, the solvent, the diluent and the additive is 1:(1-3):(1-3):(0-1).
9. Use of the lithium battery local high concentration electrolyte according to any one of claims 1 to 8 in the preparation of lithium ion batteries.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a local high-concentration electrolyte of a lithium battery as claimed in any one of claims 1 to 8.
Citation Information
Patent Citations
Locally diluted high-concentration electrolyte, preparation method thereof and lithium metal battery
CN118281286A
Electrolyte and lithium metal battery
CN118610587A
Partially-diluted high-concentration electrolyte, preparation method therefor, and lithium metal battery
WO2024139562A1